ANALISIS PEGARUH FAKTOR PRODUKSI, SOSIAL DEMOGRAFI, DAN MODAL SOSIAL TERHADAP PRODUKTIVITAS DAN KESEJAHTERAAN RUMAH TANGGA NELAYAN DI KABUPATEN TABANAN - Putra, Made Gunarsa; Setiawina, Nyoman Djinar; Murjana Yasa, I Gst. Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.05.TAHUN 2017, 2017)
As the world's largest archipelago nation, Indonesia has abundant fishery resource potential and has the longest coastline in the world after Canada. The fisheries sector become the foundation for some people who depend on fishing effort both catching and aquaculture. As society in general, fishing communities were not static. Housekeeping fisheries are actors who actively striving and working to improve their living standards, especially to increase production in order to increase income and welfare . The purpose of this study was to analyze the influence of factors of production, social demography, and social capital, social demography, and social capital through productivity on household welfare fishermen in Tabanan .
Keywords: Welfare, Productivity, Factors Production, Social Capital, Social Demography, Fishermen